PENGARUH PENGGUNAAN SMARTPHONE TERHADAP MOTIVASI BERIBADAH SANTRI PUTERA PONDOK PESANTREN NASYRUL ULUM TEGAL BUNDER PURWAKARTA CILEGON BANTEN - Saputra, Saripudin; Permata, Nuniek; Nurasiah, Iis; Asfar, Andi Hasryningsih; Munajat, Ade Agus (Bussman Journal : Indonesian Journal of Business and Management, 2025)
Rapid technological developments have a significant impact on human life, including among Islamic boarding school students. One of the most influential technologies is the smartphone. Although useful in terms of access to information and communication, excessive use can reduce worship motivation. This study aims to determine the effect of smartphone use on the worship motivation of Islamic boarding school students at the Nasyrul Ulum Islamic Boarding School. The method used is qualitative with interview techniques with 25 students from various class levels who were selected randomly. The results show that most students have and use smartphones when they are outside the boarding school. As many as 96% of respondents realized that excessive use has an impact on reducing the spirit of worship, such as praying in congregation and waking up early. In addition, 84% admitted to experiencing physical and psychological impacts due to uncontrolled use. These findings show the importance of using smartphones wisely so as not to interfere with the routine of worship and religious activities of students.